Volunteering among medical students during the COVID-19 pandemic: what should be taken into account? - Matheus Santarosa Cassiano; Nelio Neves Veiga-Junior; Luiz Gustavo Oliveira Brito; Silvia Maria Riceto Ronchim Passeri; Angelica Maria Bicudo (Revista Brasileira de Educação Médica, 2021)
Abstract: Introduction: during the COVID-19 pandemic, the universities suspended in-person activities and medical education adapted from the traditional format to virtual scenarios. Thus, the volunteering activities might improve the apprenticeship in critical situations and constitute a way to obtain competences and clinical skills. Objective: to identify the frequency of student volunteering during the COVID-19 pandemic and the associated factors. Methods: a cross-sectional study was performed targeting medical students in their last 3 years at a medical school in Brazil. Three hundred and fifty invitations were sent by email to ask students to participate in a self-administered, anonymous electronic survey during the pandemic. The primary outcome was the frequency of volunteer activities. Sociodemographic variables and characteristics of the medical students’ activities were the dependent variables for the multivariate analysis that calculated the factors associated with volunteering. Results: One hundred and twenty-five respondents (35.8% response rate) were included in the analysis (no missing data). The frequency of volunteering was 52% and most of the participants were females (63.2%) and all had access to online activities. Telemedicine was the most frequent activity (56/65). After the multivariate analysis, it was found that a family income of 5.1-10 minimal wages (OR=2.32[0.94-6.42]), expressing the ability and confidence in a pandemic situation (OR=4.91[1.49-16.2]) and considering e-learning important before the pandemic (OR=16.46[1.35-200.32]) and exposure of more than 120 minutes to social media platforms were less motivating for volunteering. Conclusion: About half of the medical students volunteered during the COVID-19 pandemic. The presence of self-confidence, with previous training in a pandemic situation motivated the students to volunteer.